PENGARUH METODE OUTING CLASS TERHADAP SIKAP PEDULI LINGKUNGAN SISWA PADA MATA PELAJARAN BIOLOGI SMAN 7 BONE - Riskawati; Ali, Muhammad; Nurmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Outing class is a fun teaching and learning activity. This learning activity can be said to be fun because playing is voluntary and creates a sense of enjoyment for students. Through play, learning activities that initially felt boring for students transform into enjoyable learning activities through play. Teaching and learning activities are not conducted indoors as is usually the case, but rather outdoors. This activity brings students closer to their environment. This research used a quantitative research with a Pre-Experimental Design with a One Group Pre-Test and Post-Test Design. The population consisted of five classes, and sampling was carried out using a purposive sampling technique. The sample was class XE 2 of SMAN 7 SMAN 7 BONE, with 26 students. Data collection techniques used in this study included providing pre- and post-test sheets to assess students' conceptual understanding and documentation. Based on the results of the research, it can be concluded that the outing class method has an effect on students' environmental awareness. Data management showed that the average pre-test score was 62 and the average post-test score was 84.42. The SPSS analysis results show a significance value of 0.000, which is less than 0.05, indicating that the use of the outing class method as a learning resource is effective in improving students' environmental awareness. Keywords: Influence, Outing Class, Environmental Awareness